The national extension policy of Malawi – lessons from implementation - Ragasa, Catherine; Mazunda, John; Kadzamira, Mariam (International Food Policy Research Institute, 2015)
The Government of Malawi put in place the National Extension Policy in 2000 to promote the provision of quality agricultural extension services. Fifteen years after its introduction, while action has been taken on some compo-nents, many key elements of the policy remain largely unimplemented. This note outlines the evidence on why much progress has not been achieved on coordination, stakeholder accountability, demand-focus, and pluralism within Malawi’s agricultural extension services. Over the past decade, public extension services have largely been under-funded while government has focused on implementing its flagship program in the agriculture sector, the Farm Input Subsidy Programme (FISP). The somewhat inconsistent impact of FISP suggests to some experts that inadequate provision of information to farmers on best agricultural production practices might account for this mixed perfor-mance. In early 2015, during extensive district-level consultations on the content of the draft National Agriculture Policy, extension services were highlighted by stakeholders as the most important priority area for increasing agri-cultural productivity in Malawi. However, tough decisions and bold actions, rather than complacency and minor fixes, will be required to transform the extension system to one that contributes significantly to improved agricultural development outcomes. This Policy Note proposes several priority areas for consideration.